Juridical analysis of the authority of judges to decide on sentencing cases from the perspective of proportionality and the principle of justice - Simbolon, Citra Irwan; Fadlan, Fadlan; Jihad, Kaspol (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: This research examines the legal regulation of judges’ authority in deciding sentencing cases through the lens of proportionality and the principle of justice, with a focus on the implementation, obstacles, and judicial efforts in the Batam District Court Class 1A. It aims to explore how judicial authority aligns with statutory provisions and societal expectations of fairness. Methodology/Approach: The study adopts a normative juridical method through literature review, complemented by an empirical juridical (sociological juridical) approach using field study. This combination provides both theoretical perspectives and empirical insights into judicial practices, creating a holistic understanding of the topic. Results/Findings: The findings indicate that the authority of judges to impose sentences is regulated under Law No. 48 of 2009 on Judicial Power and specifically Article 183 of the Criminal Procedure Code. In practice, judges at the Batam District Court Class 1A encounter several obstacles, including incomplete or absent witness testimonies and occasional internal conflicts among judicial panels. Such challenges often affect the decision-making process. However, judges continue to adhere to Article 183 as a guiding legal foundation in delivering verdicts. Conclusions: Although judicial authority in sentencing is legally well-established, its practical implementation faces obstacles. Ensuring proportionality and justice requires judges not only to apply statutory provisions but also to incorporate evolving societal values in their reasoning. Limitations: The study is limited to one court and specific cases, restricting generalizability across all Indonesian courts. Contribution: This research enriches discourse on judicial authority by integrating normative and empirical perspectives and offering practical recommendations for reinforcing proportionality and justice in judicial decision-making.